A Study on Sustainable Development Through Financial Inclusion in India (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Nationalization of banks in 1969 was the first  strike to formalize financial sector in India.  Several steps were then initiated to connect  the unbanked population with banks through  establishment of regional rural banks and  NABARD in 1976 and 1982 respectively.  Even after then lakhs of people still don’t trust  formal financial institutions and are dependent  on informal sector. Easy and secure access  of financial services is what required by the  uncatered section of the economy. This work  will explore the path through which usability  of the financial services can be increased by  the beneficiaries (customers) in a sustainable  way. The path clearly defines the importance of  affordability, accessibility, awareness, attitude  and usage towards the financial services in  augmenting the level of financial inclusion.  This work will help to comprehend the more  sustained path for effective and efficient  catering and consumption of financial services  among seeking and vulnerable section of the  economy.
Keywords: Sustainable development; Financial Inclusion; Service; Economy